2009
DOI: 10.1111/j.1365-2605.2007.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

CA repeat and RsaI polymorphisms in ERβ gene are not associated with infertility in Indian men

Abstract: Oestrogen Receptor beta (ERbeta) gene plays an important role in the regulation of fertility in both males and females. Polymorphism in CA repeat located in the flanking region of ERbeta has been shown to be associated with several diseases, but its association with male infertility has not been analysed so far. However, RsaI polymorphism (rs1256049) in exon 5 of ERbeta has been shown to be associated with male infertility in Caucasian patients. Hence, we have analysed 695 Indian men, including 443 infertile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…Significant differences have been observed in the frequency distributions of PvuII and XbaI of the ERα gene and RsaI and AluI of the ERβ gene between male infertility patients and controls in the Iranian population (Omrani et al, 2010). Khattri et al (2009) demonstrated that the ERβ polymorphism RsaI is not associated with infertility in Indian men, which is consistent with the results of the present study. Aschim et al (2005) demonstrated that the RsaI AG genotype is associated with an approximately 3-fold increase in infertility in white men, a result similar to that of Safarinejad et al (2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significant differences have been observed in the frequency distributions of PvuII and XbaI of the ERα gene and RsaI and AluI of the ERβ gene between male infertility patients and controls in the Iranian population (Omrani et al, 2010). Khattri et al (2009) demonstrated that the ERβ polymorphism RsaI is not associated with infertility in Indian men, which is consistent with the results of the present study. Aschim et al (2005) demonstrated that the RsaI AG genotype is associated with an approximately 3-fold increase in infertility in white men, a result similar to that of Safarinejad et al (2010).…”
Section: Discussionsupporting
confidence: 93%
“…For example, PvuII and XbaI in ERα have been associated with azoospermia or severe oligozoospermia in 2 reports (Kukuvitis et al, 2002;Suzuki et al, 2002), but others have drawn different conclusions (Tuttelmann et al, 2007;Lazaros et al, 2010). Moreover, RsaI and AluI in ERβ have been associated with male infertility in 2 studies (Aschim et al, 2005;Safarinejad et al, 2010), but the results could not be replicated (Khattri et al, 2009). A recent review article on the genetic causes of male factor infertility by O'Flynn et al (2010) concluded that ER gene polymorphisms should be examined further to replicate the results of earlier uncoordinated studies and to elucidate more fully the impact of these polymorphisms on male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Aschim et al, [102] reported that the RsaI polymorphism in the ERβ gene appears to be associated with infertility, showing a three times higher frequency of the heterozygous RsaI AG-genotype in the infertile group compared with controls. In contrast, in another study by Khattri et al, [103], they found no significant correlation in the incidence of the known SNPs or novel mutations between infertile and fertile men. Moreover, infertile men having ERβ mutations had normal reproductive tract and serum hormone levels.…”
Section: The Estrogen Receptors (Esr) Genes Mutationsmentioning
confidence: 69%
“…A total of 10 eligible case control studies with the publication dates ranged from 2002 to 2013 met the prespecified inclusion criteria (shown in the Figure  1), including five studies of Asian population [1921, 23, 24] and five studies of Caucasian population [5, 7, 22, 25, 26]. To determine the SNPs, two different genotyping methods such as PCR-RFLP [5, 1926] and TaqMan assays [7] were applied.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusion criteria: varicocele or testicular torsion, urinary tract infections, endocrinopathy, karyotype anomalies, Y-chromosome microdeletions, use of drugs, leukocytospermia, a BMI of 30 kg/m2 or greater.TT:49/33, CT:70/86, CC:45/45; AA:62/41, AG:77/95, GG:25/28; GG:142/152, AG:21/8, AA:1/4; GG:65/80, AG:82/63, AA:17/210.486, 0.034, 0.000, 0.132Lazaros [22]2010CaucasianPBPCR-RFLPrs2234693, rs9340799, rs1256049, rs4986938Age: 33.2 ± 67.5 years. Exclusion criteria: hypogonadotropic hypogonadism, obstructive syndromes of the seminal tract, microdeletions of the Y chromosome, karyotypic abnormalities.TT:6/20, CT:14/40, CC:9/25; AA:5/13, AG:13/43, GG:11/29; GG:26/80, AG:3/5, AA:0/0; GG:7/17, AG:12/36, AA:10/320.609, 0.652, 0.779, 0.246Khattri [23]2007AsianPBPCR-RFLPrs1256049Age: 23.24 ± 2.06 years. Exclusion criteria: obstruction, endocrinological defect, injuries, karyotypic abnormality, Y-chromosome microdeletions.GG:397/231, AG:46/21, AA:0/00.490Omrani [24]2005AsianPBPCR-RFLPrs1256049, rs4986938Exclusion criteria: genetic causes of infertility, such as Klinefelter syndrome or Ychromosome microdeletions.…”
Section: Introductionmentioning
confidence: 99%